IDENTIFIKASI JENIS TUPAI (Tupaia Sp) DI KAWASAN HUTAN ADAT BUKIT SAGU DESA SUNGAI SENA KECAMATAN SILAT HILIR KABUPATEN KAPUAS HULU - Alex, .; Anwari, Sofwan; Tavita, Gusti Eva (Universitas Tanjungpura, 2017)
Bukit Sagu Community Forest, Sungai Sena Village, Silat Hilir District, Kapuas Hulu Regency is one of the forest with natural resources diversity richness. The wildlife that live and thrive in the indigenous forest is a kind of squirrel. Squirrel one of animal which important for the ecology function, so we need to do research on